The Role of Environment and Self on Self-Efficacy in Students' Career Decision Making - Andini, Putri Fildzah; Yuliati, Lilik Noor; Hastuti, Dwi (LPPM Universitas Pendidikan Mandalika, 2024)
This research aims to assess the influence of the level of peer attachment, teacher support, parental support, self-concept, and planned career events on the career decision-making self-efficacy of high school and vocational school students. This research used a cross-sectional study design with a quantitative approach. This research was conducted on 317 students, with 157 high school students and 160 vocational school students determined by cluster random sampling. Data was collected through questionnaires and analyzed using Structural Equation Modeling (SEM) with Smart-PLS. SEM test results showed a significant positive direct influence between parental support, teacher support, and peer attachment on the self-concept of parental support, parental support, and self-concept regarding planned happenstance career, and teacher support and planned happenstance career on career decision-making self-efficacy. Apart from that, there was an indirect influence between parental support, teacher support, and peer attachment on career decision-making self-efficacy through self-concept and planned happenstance careers. Therefore, parents need to shape their children's promising planned careers so that they can have self-efficacy for making sound career decisions as well.